Optimization of Bud Set Seedling Growth in Several Sugarcane Varieties (Saccharum officinarum L.) using Liquid Organic Fertilizer from Coffee Grounds - Kasim, Nurlina; Hasmila, A.; Kaimuddin, Kaimuddin; AR, Trisnawaty (International Journal of Agriculture System, 2025)
This study aims to study and determine the growth response of several varieties of sugarcane (Saccharum officinarum L.) on the application of coffee grounds liquid organic fertilizer (POC). This research was conducted in Gattareng Village, Salomekko District, Bone Regency, South Sulawesi from April to July 2022. The research was arranged in the form of a two-factor factorial experiment with a randomized block design (RBD) as an environmental design. The first factor is the variety which consists of three varieties namely PS 881, PS 865 and Kidang Kencana. The second factor was the POC concentration of coffee grounds which consisted of four levels, namely without POC, 15 mL/L, 30 mL/L and 45 mL/L. The results showed that the combination of the PS 865 variety with 15 mL/L POC coffee grounds gave results on the parameters of stem diameter (18.67 mm), fresh stem weight (66.50 g), stem dry weight (33.29 g) and root volume (35.33 mL). The PS 865 variety gave the best results on the parameters of plant height (34.61 cm), number of leaves (9.50), root wet weight (23.0 g), root dry weight (6.37 g) and root length (105 g). .92 cm) sugarcane seeds. POC coffee grounds 45 mL/L gave the best results on the parameters of plant height (33.67 cm), root wet weight (22.11 g), and root dry weight (5.86 g) of sugarcane seedlings.